Dinaciclib Induces Anaphase Catastrophe in Lung Cancer Cells via Inhibition of Cyclin Dependent Kinases 1 and 2 - Danilov, Alexey V. (Mol Cancer Ther, 2016)
Despite advances in targeted therapy, lung cancer remains the most common cause of cancer-related mortality in the United States. Chromosomal instability is a prominent feature in lung cancer and because it rarely occurs in normal cells, it represents a potential therapeutic target. Our prior work discovered that lung cancer cells undergo anaphase catastrophe in response to inhibition of cyclin-dependent kinase 2 (CDK2), followed by apoptosis and reduced growth. In this study, the effects and mechanisms of the multi-CDK inhibitor dinaciclib on lung cancer cells were investigated. We sought to determine the specificity of CDK-dependent induction of anaphase catastrophe. Live cell imaging provided direct evidence that dinaciclib caused multipolar cell divisions resulting in extensive chromosome missegregation. Genetic knockdown of dinaciclib CDK targets revealed that repression of CDK2 and CDK1, but not CDK5 or CDK9 triggered anaphase catastrophe in lung cancer cells. Overexpression of CP110, which is a mediator of CDK2 inhibitor-induced anaphase catastrophe (and a CDK1 and 2 phosphorylation substrate), antagonized anaphase catastrophe and apoptosis following dinaciclib treatment. Consistent with our previous findings, acquisition of activated KRAS sensitized lung cancer cells to dinaciclib-mediated anaphase catastrophe and cell death. Combining dinaciclib with the mitotic inhibitor Taxol augmented anaphase catastrophe induction and reduced cell viability of lung cancer cells. Thus, the multi-CDK inhibitor dinaciclib causes anaphase catastrophe in lung cancer cells and should be investigated as a potential therapeutic for wild-type and KRAS mutant lung cancer, individually or in combination with taxanes.